Recurrence after microwave ablation of liver malignancies: a single institution experience. Issue 5 (11th October 2012) - Groeschl, Ryan T.; Wong, Ray K.; Quebbeman, Edward J.; Tsai, Susan; Turaga, Kiran K.; Pappas, Sam G.; Christians, Kathleen K.; Hohenwalter, Eric J.; Tutton, Sean M.; Rilling, William S.; Gamblin, T. Clark
Abstract Background Microwave ablation (MWA) is increasingly used to achieve local control for liver tumours. This study sought to examine a monocentric experience with MWA, with a primary hypothesis that primary tumour histology was a significant predictor of early recurrence. Methods Retrospective single‐institution review identified consecutive patients with liver tumours treated by MWA. Cox proportional hazards models assessed significance of prognostic variables. Results Seventy‐two patients (43 female, 60%) underwent 83 MWA procedures for 157 tumours. Tumour histologies included hepatocellular cancer (10 operations), colorectal metastases (39), metastatic carcinoid (20) and other (14). The median tumour size was 2.0 cm. A concomitant liver resection was performed in 50 cases (60%). Crude peri‐operative morbidity and mortality rates were 16% and 1%, respectively. The median follow‐up was 16 months. Ablations were complete for 149 out of 157 tumours (95%). The median overall and recurrence‐free survivals were 36 and 18 months, respectively. There was no difference in time to recurrence between the primary tumour types. In multivariable models, recurrence‐free survival was independently associated with the use of neoadjuvant [hazard ratio (HR): 2.90, 95% confidence interval (CI): 1.09–7.76, P = 0.034] and adjuvant chemotherapy (HR: 0.36, 95% CI: 0.15–0.82, P = 0.016). Conclusions MWA is a safe and feasible approach for local control of liver tumours. While chemotherapy administration was associated with time to recurrence after MWA, larger studies are needed to corroborate these findings.